The effects of IFRS adoption on taxation in Nigerian manufacturing companies - Adegbbite, Tajudeen Adejare (Wpływ implementacji międzynarodowych standardów sprawozdawczości finansowej na wysokość opodatkowania nigeryjskich przedsiębiorstw produkcyjnych, 2020)
This study examined the effect of IFRS adoption on manufacturing companies’ tax payable from 2012 to 2018. Data gathered from the annual reports of fifty selected Nigerian listed companies were scrutinised employing PPMC and panel data methodology to quantify the effect of IFRS adoption on tax payable. It revealed that Profit before tax (PBT) caused a positive and significant effect on TAXATION, whereas Depreciation (DEPR), Shareholders’ Funds (SHDFUD), Long-term debt (LGTDEBT), and Noncurrent Asset (NONCURASET) impacted on TAXATION negatively. This showed that an surge in DEPR, SHDFUD, LGTDEBT and NONCURASET diminished TAXATION in manufacturing companies. Conclusively, IFRS adoption significantly downplayed manufacturing companies’ tax payable because organisations circumspectly and lawfully circumvent or reduce the tax payable through depreciation claimed on existing assets, the procurement of new noncurrent assets, and long term debt (leverage). It is advocated that there should be monitoring mechanism devices put in motion by the government to monitor procurement by companies, impairment of assets and debts acquired transparently, in order to deter the unnecessary and artificial reduction in tax payable
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 4, s. 1-15
Keywords: depreciation; taxation; shareholders' funds; long-term debt; noncurrent asset; IFRS; amortyzacja; opodatkowanie; kapitał własny; zobowiązania długoterminowe; aktywa trwałe; MSSF